2018 43rd International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) 2018
DOI: 10.1109/irmmw-thz.2018.8510069
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated 200-GHz Graphene FET Based Receiver

Abstract: A receiver composed by a graphene FET 200-GHz mixer and a 1-GHz intermediate frequency amplifier integrated on a silicon substrate was modelled, fabricated and characterized. This is the first demonstration of a millimeter wave integrated receiver based on graphene FETs. The receiver conversion loss is measured to be 25 dB across the 185-205-GHz band with 16 dBm of local oscillator pump power, which is in good agreement with the circuit simulations. The simulations show that the receiver conversion loss can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Finally, Table 3 summarizes a performance comparison between the described prototype and other recently reported graphene-based mixers capable of working above 100 GHz. References [32]- [34] describe MMIC circuits based on GFETs. Although they reported good conversion gain values, LO signals with frequency around 100 [33], [34] and 200 GHz [32], and power level between 8 and 16 dBm are used, requiring external high-performance frequency multipliers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, Table 3 summarizes a performance comparison between the described prototype and other recently reported graphene-based mixers capable of working above 100 GHz. References [32]- [34] describe MMIC circuits based on GFETs. Although they reported good conversion gain values, LO signals with frequency around 100 [33], [34] and 200 GHz [32], and power level between 8 and 16 dBm are used, requiring external high-performance frequency multipliers.…”
Section: Discussionmentioning
confidence: 99%
“…References [32]- [34] describe MMIC circuits based on GFETs. Although they reported good conversion gain values, LO signals with frequency around 100 [33], [34] and 200 GHz [32], and power level between 8 and 16 dBm are used, requiring external high-performance frequency multipliers. On the other hand, works [8] and [42] present subharmonic mixers based on macroscopic graphene sheets, following a design approach similar to that used in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the circuit design and fabrication of the wide bandwidth THz mixers are challenging tasks. In recent years, it was shown that the graphene field-effect transistors (GFETs), owing to their linear output characteristics and relatively high carrier mobility, have a great potential for development of the GFET based high-frequency mixers [3][4][5]. But most of the demonstrated GFET mixers reveals rather narrow RF and/or IF bandwidths [6].…”
Section: Introductionmentioning
confidence: 99%